Strategic Regional Planning For Sustainable Urban Growth: A Case Study From Hooghly District Of West Bengal, India (Journal of Namibian Studies : History Politics Culture, 2023)
In West Bengal, India urbanization provides some difficulties. It also gives opportunities for sustainable development. This study explores main urban matters such as water scarcity, electricity infrastructure, transportation issues, green spaces, air pollution, neatness, housing affordability, and community involvement in government planning and developmental initiatives. Transportation issues, green spaces and air pollution are the significant issues, which provides challenges in social equity such as housing affordability and community collaboration. It demands integrated planning approaches and targeted interventions to handle the issues related to this. These demands include the investments in advancements of the infrastructure, developing sustainable mobility options, increasing green infrastructure, implementing rigorous environmental management rules, and also inclusive housing strategies. Moreover, improving community collaboration and administration transparency is also an important aspect to improve inclusive and resilient urban enhancement in West Bengal. The policy makers and stakeholders can make efforts towards creating sustainable, reliable, and equitable cities that focus on environmental conservation and fulfil various demands of the urban residents.